Single institution validation of a modified graded prognostic assessment of patients with breast cancer brain metastases. (2nd February 2018) - Tai, Cheng-Hung; Wu, Cheng-Chia; Hwang, Mark E; Saraf, Anurag; Grubb, Christopher; Jani, Ashish; Lapa, Matthew E; Andrews, Jacquelyn I S; Isaacson, Steven R; Sonabend, Adam M; Sheth, Sameer A; McKhann, Guy M; et al.
Aim: The number of breast cancer brain metastases is a prognostic clinical variable in the modified graded prognostic assessment (GPA) Index for breast cancer.Patients & methods: We retrospectively gathered data from 127 breast cancer patients who underwent radiation therapy for brain metastasis. Patients were stratified by both breast GPA and modified breast GPA scores, and survival was determined using the Kaplan–Meier curves and Cox proportional hazards model.Results & Conclusion: The Kaplan–Meier curve for patients under the breast GPA classification were not significant, but were significant under the modified breast GPA classification. The inclusion of number of brain metastases into the modified breast GPA index improved prognosis, thus validating the use of the modified breast GPA in prognosticating patient outcome.